Approximate solutions of equations defined by complex spherical multiplier operators - C. P. Oliveira (Journal of Applied Mathematics)
This paper studies, in a partial but concise manner, approximate solutions of equations defined by complex spherical multiplier operators. The approximations are from native spaces embedded in Sobolev-type spaces and derived from the use of positive definite functions to perform spherical interpolation.